BURGELIJK WETBOEK (Menelusuri Sejarah Hukum Pemberlakuannya di Indonesia) - Erie Hariyanto (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2009)
Burgelijk Wetboek or the book of civil law is historicallyderived from Dutch. It has been applied on the basis ofconcordancy principle; in fact, the legislative institutionhas not published civil laws that being coded and unifiedyet. It is urgent to apply new laws that exclusively managelaw of contract (in particular or general) as a part of civillaws, in order to support the economic activity of nation.Dutch has already revised their own Burgelijk Weboek thathas been applied in Indonesia.